2021
DOI: 10.5817/cp2021-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Harmonious and obsessive involvement, self-esteem, and well-being. A longitudinal study on MMORPG players

Abstract: Starting from the dualistic model of passion by Vallerand and colleagues (2003), this study aimed to identify “obsessive” and “harmonious” involvements in MMORPGs and to verify their relationships with players’ self-esteem and well-being. An international sample of 147 MMORPG players participated in a longitudinal design filling out for 3 times an online questionnaire measuring game involvement (in terms of Internet Gaming Disorder [IGD] symptoms, time spent playing the video game, sense of presence while play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 85 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…Players at the national level have generally had greater success and reputation as a result of participating at the national level, representing their nation, and frequently receiving praise from the public and media. (Sibilla et al, 2021) [13] . National-level athletes feel more confident about themselves since they are part of a select group of athletes who have achieved remarkable success on a national level, which is reinforced by this increased degree of recognition and achievement.…”
Section: Discussionmentioning
confidence: 98%
“…Players at the national level have generally had greater success and reputation as a result of participating at the national level, representing their nation, and frequently receiving praise from the public and media. (Sibilla et al, 2021) [13] . National-level athletes feel more confident about themselves since they are part of a select group of athletes who have achieved remarkable success on a national level, which is reinforced by this increased degree of recognition and achievement.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that the different nature of engagement in playing video games is an important factor in whether this activity positively or negatively affects adolescents' academic performance and schoolwork. Sibilla et al (2021) found that increased time spent playing video games was a characteristic of obsessive involvement, but not of harmonious involvement in playing video games. Thus, time spent playing video games may be related to motivation for playing video games, but this depends on whether there is an obsessive or harmonious passion for playing video games.…”
Section: Introductionmentioning
confidence: 93%
“…The two types of passion for gaming have been linked to different patterns of time spent playing (e.g., Lafrenière et al, 2009;Sibilla et al, 2021), so time spent playing on a typical school day may mediate the relationship between obsessive passion for gaming and behavioral school engagement. After all, spending time in one activity, regardless of other obligations, means less time for other activities.…”
Section: H3mentioning
confidence: 99%
“…Time spent on an activity is thus a core marker of passion. Indeed, gaming studies have consistently shown that individuals who have a passion for gaming tend to spend more time gaming (Marsh et al, 2013; Sibilla et al, 2021). Therefore, we hypothesize:Hypothesis Passion for gaming relates positively to the number of hours people spend on gaming.…”
Section: Theoretical Frameworkmentioning
confidence: 99%